Dual Primary Gastric and Rectal Adenocarcinoma: A Case Report with Management Insights - Dastjerdi, Ali; Samami, Elham; Javadinia, Seyed Alireza; Anvary, Maryam; Kazemzadeh, Asghar; Molavi, Mehdi; S Welsh, James (Galen Medical Journal, 2025)
Background: Dual primary malignancies, including colorectal (CRC) and gastric cancers (GC), are complicated cases due to the complexity of managing patients. Case Report: This case report presents a 62-year-old male patient with rectal and gastric adenocarcinomas. Initially, rectal adenocarcinoma after a complaint of hematochezia was diagnosed by prognostic modalities. The patient received total neoadjuvant therapy with FOLFOX chemotherapy and chemoradiotherapy. After surgery, a complete pathological response was obtained. A few months later, gastric adenocarcinoma with persistent heartburn was detected through esophagogastroduodenoscopy (EGD). total neoadjuvant therapy with FOLFOX chemotherapy and chemoradiotherapy followed by total gastrectomy were prescribed. After gastrectomy, a complete pathological response was obtained. Conclusion: This case of synchronous CRC and GC, diagnosed 5 months apart, underscores the pivotal role of early detection and multidisciplinary management in achieving favorable outcomes. Complete pathologic responses in both malignancies following tailored TNT with FOLFOX and FLOT regimens, combined with surgical interventions, highlight the efficacy of personalized treatment strategies, even in resource-constrained settings. Continued research is essential to optimize diagnostic protocols, refine therapeutic approaches, and improve access to genetic testing for synchronous and metachronous malignancies, promoting equitable cancer care globally.